Effect of Alkali Treatment and Molding Temperature on Flexural and Impact Properties of Coir-Fibre-Epoxy Composite. Issue 4 (July 2015) - Tai, C. K.; Ahmad, R.; Akil, H. M.; Ratnam, M. M.
The combined effects of alkali treatment and compression molding temperature on the flexural strength and impact resistance of woven coir fibre composites are investigated. Ten pieces of composites plates made from single-layer woven coir fibre fabricated under different process parameters were used in the study. Five pieces of the coir woven fibre were treated with 6% sodium hydroxide (NaOH) solution while another five were left untreated. The compression molding temperature were varied between room temperature (25°C), 50°C, 75°C, 100°C and 125°C. The flexural properties of the composite were evaluated using the three-point flexural test, while the impact resistance was investigated by drop weight impact tests using a specially designed indenter. The indentation radius on each test specimen was measured using a 3-D metrology system and the depth of indentation was determined from the geometry of the indenter. The results show that the maximum flexural load to failure is improved by 38.9% when the fibres were treated and the compression molding temperature is increased to 125°C. The flexural modulus generally decreased with increase in the molding temperature. The depth of indentation in the treated coir woven composites is lower than that of untreated fibre composite at all molding temperatures. The impact resistance of both untreated and treated fibre composites decreased with the increase in the compression molding temperature. Composites fabricated by molding at room temperature, 50°C and 75°C using treated fibre produced the best impact properties.